HOUT-01. ALOPECIA SYMPTOM IMPACT SCALE (ASIS): MEASURING THE SYMPTOMS OF ALOPECIA AND THEIR IMPACT IN PATIENTS WITH PRIMARY BRAIN TUMORS. (11th November 2019) - Mendoza, Tito; Rowe, Lindsay; Vera, Elizabeth; Acquaye, Alvina; Gilbert, Mark; Armstrong, Terri
Abstract: INTRODUCTION: Alopecia manifests in many cancer patients receiving therapy. These patients may experience similar physical symptoms and impairment as patients with autoimmune alopecia areata. The Alopecia Areata Symptom Impact Scale (AASIS) was originally validated for patients with autoimmune disorder. However, the validity and reliability of the AASIS among primary brain tumor (PBT) patients has not been evaluated. METHODS: A cross sectional survey of 100 PBT patients was conducted as part of an IRB approved prospective protocol using structured questionnaires and open-ended responses. Participants completed the AASIS to measure symptoms of alopecia areata and their impact on daily functioning along with the Body Image Scale (BIS) to assess the prevalence of body image disturbance. Analyses included factor analysis to determine the number and nature of underlying constructs, Cronbach's alphas to assess reliability, and correlational analysis to establish concurrent validity. RESULTS: Patients' median age was 48(range 23– 74), and 56% were male. Glioblastoma was most common (32%); low grade tumors (I and II) were 30% of diagnoses. The median time from initial diagnosis was 5 years (range 0–22), and 64% of patients had a KPS of 90–100. An item from the AASIS, 'body hair or eyelashes loss', was deemed to be irrelevant, rated low by PBT patients and was removed. Factor analysis revealed 3 underlying constructs: physical (e.g. itchy skin, scalp hair loss), affective (e.g. feeling anxious, feeling sad) symptoms, and impact of alopecia (e.g. work, quality of life) with Cronbach's alphas of 0.78, 0.89 and 0.96, respectively. The BIS had the highest correlation with the affective symptom subscale (0.58, p< .001). CONCLUSION: Our results demonstrate the desired reliability and validity for use in studies examining alopecia and its impact in PBT patients. Dropping the term 'areata', the modified tool is now ASIS, and can be implemented in future studies.